2022
DOI: 10.1097/pas.0000000000001934
|View full text |Cite
|
Sign up to set email alerts
|

Morules But Not Squamous Differentiation are a Reliable Indicator of CTNNB1 (β-catenin) Mutations in Endometrial Carcinoma and Precancers

Abstract: Although collectively regarded as "squamous differentiation (SD)" in endometrial endometrioid carcinoma (EEC) and atypical hyperplasia/endometrioid intraepithelial neoplasia (AH/EIN), morules (often referred to as "squamous morules") and true SD may represent two distinct phenomena. Here, we explored the distinction between morules versus SD and investigated the association of morules and SD with CTNNB1 mutations. A total of 270 cases of EEC and AH/EIN were studied, including EEC with (n = 36) or without (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(101 reference statements)
3
13
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41] Our previous study confirmed that morules are a reliable indicator of CTNNB1 (β-catenin) mutations in endometrial carcinoma and precancers. 10 Morules were absent in all EMPs included in this study. Rare cases of EMP with "squamous morules" or "morular metaplasia" have been reported in the literature.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…[34][35][36][37][38][39][40][41] Our previous study confirmed that morules are a reliable indicator of CTNNB1 (β-catenin) mutations in endometrial carcinoma and precancers. 10 Morules were absent in all EMPs included in this study. Rare cases of EMP with "squamous morules" or "morular metaplasia" have been reported in the literature.…”
Section: Discussionmentioning
confidence: 77%
“…In our cohort, criteria for the diagnosis of EMP includes either an intact polypod-shaped lesion or, when the lesion is fragmented, a combination of stroma, glands, and vasculature characteristic of EMPs. Interpretation of β-catenin, PAX2, and PTEN was performed as per our recent publications 9,11,18 . Due to the fact that sporadic loss of PAX2 and PTEN is observed in a small proportion of normal endometria (typically, in <10% of endometrial glands), the absence of staining for these markers in ≥5% of glands was considered loss of expression 9 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent FIGO 1 adenocarcinoma, diagnosed 5 weeks later, was aberrant for Pax2, Pten, and β-catenin, and concordantly exhibited squamous metaplasia, commonly seen in CTNNB1 -mutant endometrioid adenocarcinomas. 22 , 23 , 33 Thus, this is another example of marker concordance in a precursor lesion that was diagnosed as NAH by histologic features, but in fact, is revealed by the 3-marker panel to be a neoplastic precursor mimicking a non-neoplastic process. It is also another example of the 3-marker panel’s ability to detect aberrancy even with suboptimal sampling (which seems likely in this case given the extremely short time interval between index and progressor).…”
Section: Resultsmentioning
confidence: 91%